2020
DOI: 10.1002/mp.13971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pixelated large format CMOS sensor for x‐ray microbeam radiotherapy

Abstract: Purpose Current techniques and procedures for dosimetry in microbeams typically rely on radiochromic film or small volume ionization chambers for validation and quality assurance in 2D and 1D, respectively. Whilst well characterized for clinical and preclinical radiotherapy, these methods are noninstantaneous and do not provide real time profile information. The objective of this work is to determine the suitability of the newly developed vM1212 detector, a pixelated CMOS (complementary metal‐oxide‐semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Due to their high spatial resolution, the MIMOSA-28 sensors are well suited for precision particle fluence measurements [21], similar to those required for characterizing the fluence profile at the MBC slits. This corroborates previous works on X-ray minibeam therapy [18] and pMBRT [19], which already indicated promising potential of CMOS technology for providing high-resolution dosimetry in minibeam experiments. The CMOS sensor high resolution revealed a shoulder at the base of the slit lateral fluence profiles at small distance to the collimator exit (Figure 4d), stemming from edge scattering effects at the corners of the MBC slits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to their high spatial resolution, the MIMOSA-28 sensors are well suited for precision particle fluence measurements [21], similar to those required for characterizing the fluence profile at the MBC slits. This corroborates previous works on X-ray minibeam therapy [18] and pMBRT [19], which already indicated promising potential of CMOS technology for providing high-resolution dosimetry in minibeam experiments. The CMOS sensor high resolution revealed a shoulder at the base of the slit lateral fluence profiles at small distance to the collimator exit (Figure 4d), stemming from edge scattering effects at the corners of the MBC slits.…”
Section: Discussionsupporting
confidence: 91%
“…Experimental characterization of the brass MBC was performed with clinical carbon ion beams at the Marburg Ion-Beam Therapy Center (MIT), employing a high-resolution CMOS monolithic active pixel sensor, the MIMOSA-28 [17] sensor originally developed for the STAR experiment at RHIC. CMOS sensors have been presented in the literature to be useful tools for X-ray minibeam experiments [18] and recently also for pMBRT [19]. The MIMOSA-28 sensor employed in our study has already been characterized for various incident ion beams [20], demonstrating its capability of discerning secondaries and primaries based on their energy loss in the sensor.…”
Section: Introductionmentioning
confidence: 91%
“…Relative Dose (log) manufacturer [43], and the film response would be especially sensitive to any slight miscalibration in this region. This again highlights the versatility of sensitive CMOS detectors for measurement of low dose valleys as previously demonstrated for x-ray microbeams [25].…”
Section: Jinst 18 P03014supporting
confidence: 64%
“…The vM2428 detector, also referred to as Athena or LASSENA [23], is a large-format Complementary Metal-Oxide-Semiconductor (CMOS) sensor designed for scientific and medical x-ray imaging. Although it was not designed for pMBRT, previous investigations at University College Hospitals London NHS Foundation Trust (UCLH) [24] have demonstrated that the detector was a viable candidate for use with proton beams, whilst the precursor to the vM2428 detector, the vM1212 detector, was found to be able to measure static and dynamic x-ray microbeams in a Small Animal Radiation Research Platform (SARRP) [25,26]. The vM2428 detector's specifications are described further in table 1.…”
Section: Cmos Detectormentioning
confidence: 99%
“…The generated x-rays traveled through a 0.8 mm beryllium window, aluminum or copper filters of different thickness, and a microbeam collimator (field size , divergent slits of [23] , [24] ), which was positioned 50 cm from the focal spot. The absorber thickness of the collimator was adjusted to the maximum photon energy for less than 0.25 % leakage radiation.…”
Section: Methodsmentioning
confidence: 99%